The Effect of Integrated Firm’s Reporting on Firm’s Performance - Nurim, Yavida; Wardoyo, Cipto; Astuti, Sri; ., Zuhrohtun (KnE Social Sciences, 2020)
This study investigates the effect of integrated firm’s reporting on firm’s performance. The integrated financial reporting contains of financial, good corporate governance (GCG) and sustainability reporting that shows company’s responsibility to capital providers, environment and social. The important question is whether more disclosure indicates more informative for decision maker. Therefore, it is important to identify which reporting useful for primary users. This study examines 108 public comphanies that granted ISRA (Indonesia Sustainability Reporting Award) from 2013-2017 for firm’s performance, GCG index, and sustainability index. The result shows that information for capital providers can be used for investment and credit decision. This finding indicates company faces agency conflict, so company’s disclosure dedicates for primary users, namely creditor and shareholder. This finding also indicate that earnings more informative than good corporate governance and sustainability reporting. It may show the concentrated ownership in Indonesia encourages management to behave less aggressive. Keywords: Tobin’s Q, integrated firm’s reporting, good governance, sustainability reporting, earnings